AFTIMOON --(CUSCUTA REFLEXA) A GEM FROM UNANI LITERATURE (International Journal of Food and Nutritional Sciences, 2022)
Unani System of medicine is universal in its origin and exists into south Asian countries particularly in India. In this system most of the treatments depend upon plants. Unani Drugs consist of naturally occurring mostly herbal medicine. India has such a diverse climate that many kinds of medicinal herbs and plants are available in this country. Cuscuta also known as dodder(aftimoon) is a parasitic plant. It has no chlorophyll and cannot make its own food by photosynthesis. Instead, it grows on other plants, using their nutrients for its growth.